Death at the opposite ends of the Eurasian continent Mortality trends in Taiwan and the Netherlands - Shepherd, John R.; Engelen, Theo; Yang Wen-Shan (Life at the Extremes, 2011)
Historical demographers since Malthus have characterized the West-European and Chinese demographic regimes as systems under low and high pressure, respectively. This volume examines the operation of the positive check at the two ends of the Eurasian continent by taking the Netherlands and Taiwan as representatives of the West-European and Chinese mortality regimes. Are these cases as different as the low and high pressure contrast implies? The volume opens with a cluster of chapters dealing with long term trends in mortality and the accompanying changes in causes of death (Chapters 1 through 4 ). Both Taiwan and the Netherlands witnessed steady improvements in public health, disease prevention, medical care, and living conditions in the periods described; these trends are discussed in Chapters 5 though 8. The third cluster of chapters analyzes the factors affecting maternal and infant mortality (Chapters 9 through 12). Finally, in Chapter 13, the accuracy of Taiwan's censuses and death reporting is assessed.